2022
DOI: 10.1002/hep.32439
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes medications and risk of HCC

Abstract: Type 2 diabetes mellitus is a recognized risk factor for HCC in patients with liver disease, independent from the etiology of their liver disease. Hence, prevention and treatment of type 2 diabetes mellitus and its underlying cause, insulin resistance, should be considered a treatment target for patients with liver disease. The drug armamentarium for diabetes is wide and consists of agents with insulin‐sensitizing activity, agents that stimulate insulin secretion, insulin itself, and agents that reduce gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 137 publications
0
57
1
Order By: Relevance
“…(83) Similarly, increasing evidence has suggested the potential hepatoprotective effects of some antidiabetic drugs. (84,85) Metformin is a biguanide compound that improves insulin resistance by targeting the enzyme AMP-activated protein kinase, which induces the muscle uptake of glucose from the blood. In 2005, it was first reported that the use of metformin in patients with T2DM may reduce their risk of cancer.…”
Section: Medications For Diabetes Mellitus and Hcc Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…(83) Similarly, increasing evidence has suggested the potential hepatoprotective effects of some antidiabetic drugs. (84,85) Metformin is a biguanide compound that improves insulin resistance by targeting the enzyme AMP-activated protein kinase, which induces the muscle uptake of glucose from the blood. In 2005, it was first reported that the use of metformin in patients with T2DM may reduce their risk of cancer.…”
Section: Medications For Diabetes Mellitus and Hcc Riskmentioning
confidence: 99%
“…(87, 91) Singh et al also conducted a post hoc analysis of randomized controlled trials, and their results did not reveal any significant association between antidiabetic medication use and the risk of HCC (90). Thus, further validation based on evidence from randomized clinical trials is warranted.Insulin is a potent mitogen associated with the upregulation of various growth factors that stimulate several signaling pathways related to cell proliferation and apoptosis inhibition (84). HCC in patients with diabetes 16 Epidemiologic evidence indicates that the insulin secretion rate influences cancer risk or prognosis, and patients with diabetes treated with insulin have a higher risk of HCC.…”
mentioning
confidence: 99%
“…glitazones), suppress oncogenic molecular pathways in multiple cancer types, including HCC, likely with their pleiotropic effects besides insulin sensitization and adenosine monophosphate-activated protein kinase (AMPK) activation. 49…”
Section: Anti-diabetic Agentsmentioning
confidence: 99%
“…54 In contrast, other commonly used anti-diabetics, i.e., sulfonylureas, a-glucosidase inhibitor, and insulin when combined with other drugs, likely increase HCC risk according to retrospective and prospective clinical studies. 49,53,54 Clinical evidence is still lacking, but new classes of anti-diabetic agents such as sodium glucose cotransporter-2 (SGLT2) inhibitors and glucagon-like peptide-1 (GLP1) receptor agonists have shown to elicit anti-HCC effect in cell culture systems and rodent models of NAFLD-driven HCC, 49 suggesting their role in HCC chemoprevention to be determined in future studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, retinoids significantly ameliorated hyperglycemia, insulin resistance, and hepatic steatosis in a mouse model of NAFLD ( 74 , 75 ). Hyperglycemia and hyperinsulinemia, which are frequently complicated with NAFLD, are also risk factors for HCC ( 76 ). Thus, from dual aspects, retinoid supplementation would be an efficient strategy to prevent HCC development in patients with NAFLD.…”
Section: Prevention Of Iron-induced Liver Damage By Nutrientsmentioning
confidence: 99%